\[\boxed{\text{866\ (866).\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[1)\ А\ ( - 2;\ - 6,6):\]
\[1,8 \cdot ( - 2) - 3 = - 3,6 - 3 =\]
\[= - 6,6\ \Longrightarrow проходит.\]
\[2)\ В\ (1;1,2):\ \]
\[1,8 - 3 = - 1,2 \Longrightarrow не\ проходит;\]
\[3)\ С\ (0; - 3):\ \]
\[0 - 3 = - 3 \Longrightarrow проходит;\]
\[4)\ \text{D\ }(5;7):\ \ \]
\[1,8 \cdot 5 - 3 = 9 - 3 = 6 \Longrightarrow\]
\[\Longrightarrow не\ проходит.\]
\[\boxed{\text{866.\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\(1){\ (a - 1)}^{3} - 9 \cdot (a - 1) =\)
\[= (a - 1)(a - 4)(a + 2)\]
\[(a - 1)^{3} - 9 \cdot (a - 1) =\]
\[= (a - 1)\left( (a - 1)^{2} - 9 \right) =\]
\[= (a - 1)(a - 1 - 3)(a - 1 + 3) =\]
\[= (a - 1)(a - 4)(a + 2)\]
\[(a - 1)(a - 4)(a + 2) =\]
\[= (a - 1)(a - 4)(a + 2) \Longrightarrow\]
\[\Longrightarrow тождество.\]
\[2)\ \left( x^{2} + 1 \right)^{2} - 4x^{2} =\]
\[= (x - 1)²(x + 1)²\]
\[\left( x^{2} + 1 \right)^{2} - 4x^{2} =\]
\[= \left( x^{2} + 1 - 2x \right)\left( x^{2} + 1 + 2x \right) =\]
\[= (x - 1)^{2}(x + 1)^{2}\]
\[(x - 1)^{2}(x + 1)^{2} =\]
\[= (x - 1)^{2}(x + 1)^{2} \Longrightarrow\]
\[\Longrightarrow тождество.\]